2017
DOI: 10.1016/j.wneu.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Cavernous Carotid Surgical Complications: Evaluation of a Simulated Perfusion Model

Abstract: Objective Endoscopic surgical treatment of pituitary tumors, lateral invading tumors, or aneurysms requires surgeons to operate adjacent to the cavernous sinus. During these endoscopic endonasal procedures, the carotid artery is vulnerable to surgical injury at its genu. The objective of this simulation model was to evaluate trainees regarding management of a potentially life-threatening vascular injury. Methods Cadaveric heads were prepared in accordance with the Oregon Health & Science University body dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…In addition to avoidance of ICA injury, an increased preparedness for its management may improve outcomes after a carotid artery injury . To achieve this goal, several endonasal carotid injury models have been developed . These include the previously mentioned sheep model, perfusion‐based cadaveric models, and noncadaveric synthetic models.…”
Section: Complicationsmentioning
confidence: 99%
“…In addition to avoidance of ICA injury, an increased preparedness for its management may improve outcomes after a carotid artery injury . To achieve this goal, several endonasal carotid injury models have been developed . These include the previously mentioned sheep model, perfusion‐based cadaveric models, and noncadaveric synthetic models.…”
Section: Complicationsmentioning
confidence: 99%
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Various score‐based methods were also used, including procedure scores, global rating scale (GRS), OSATS (Objective Structured Assessment of Technical Skills in Surgery) and the GOALS (Global Operative Assessment of Laparoscopic Skills) scale. Seven of the 23 studies were RCTs and 16 were cohort studies. Of the seven RCTs, three compared cadaveric simulation with no simulation training, and four compared cadaveric simulation with low‐fidelity simulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations